Description of the voided urinary microbiota in asymptomatic prepubertal children – A pilot study. Issue 4 (August 2021) - Fredsgaard, Lea; Thorsteinsson, Kristina; Bundgaard-Nielsen, Caspar; Ammitzbøll, Nadia; Leutscher, Peter; Chai, Qing; Jensen, Ann-Maria; Sørensen, Suzette; Pedersen, Lia M.; Hagstrøm, Søren; Arenholt, Louise T.S.
Summary: Background: Recently, it has been established that the urine of a healthy adult bladder contains a microbiota and that urinary dysbiosis may be involved in the development of urinary tract diseases. The urinary microbiota and its relation to bladder health and disease in children is yet to be established. The objective of the present study was to investigate the voided urinary microbiota in asymptomatic prepubertal children. Study design: Thirty asymptomatic children (15 boys and 15 girls) participated in the study. Bacterial DNA in "clean-catch" midstream urine (CC MSU) samples was analysed using Illumina MiSeq sequencing of the V4 region of the bacterial 16 S rRNA gene. All children had normal bladder function as ensured by uroflowmetry, ultrasonic post-void residual, and frequency-volume charts. Bladder-related parameters and gender comparisons were analysed statistically by parametric and non-parametric tests. Alpha diversity, beta diversity, and a Venn diagram were used to analyse sequencing data. Results: All CC MSU samples contained bacterial DNA. The voided urinary microbiota differed significantly between girls and boys in terms of operational taxonomic unit (OTU) richness, Shannon diversity index, and relative abundances of bacterial genera, but not for evenness. The urine of girls was dominated by Prevotella (18.2%), Porphyromonas (12.9%), Ezakiella (8.1%), Prevotella 6 (7.4%), and Dialister (7.0%) . Porphyromonas (22.4%) was the most abundant genus in boys, followed by Ezakiella (12.0%), Campylobacter (11.6%), Prevotella (8.6%), and Dialister (3.7%) . Girls had 10 unique core OTUs, whereas boys had no unique core OTUs. Porphyromonas appeared as a shared core OTU between genders. Discussion: Contrary to previous findings, this study found significant differences in the voided urinary bacterial composition among asymptomatic prepubertal children. Moreover, the bacterial composition diverged from that found among healthy adults by other research groups. Among adults, the gender specific urinary microbiota has been hypothesised to be caused by anatomical differences in the reproductive organs and differences in sex hormone levels. This could also be evident for asymptomatic prepubertal children as sex hormone levels are different even at the prepubertal stage. The limitations of the study encompass small sample size and urine collection by CC MSU with risk of contamination from surrounding areas. Conclusions: This study documents that CC MSU samples of asymptomatic prepubertal children are not sterile. The composition of the voided urinary microbiota seems gender specific and unequal to that of healthy adults. The role of the urinary microbiota in paediatric urological disorders should be considered in future studies.